Short Communication : Genetic diversity in upland rice of Assam assessed through SSR markers - Rathi, Sunayana; Yadav, R. N. S.; Pathak, K.; Sarma, R.N. (The Indian Journal of Genetics and Plant Breeding, 2017)
The genetic diversity in 100 upland rice germplasm of Assam, was analyzed using 120 SSR markers, of which 98 (81.66%) showed useful polymorphism with a total of 183 alleles. The number of alleles ranged from one to three with an average value of 1.867 per locus. The markers showed an average effective number of alleles to be 1.73, average Nei’s gene diversity was 0.393, and average Shannon’s Information Index was 0.556. The effective number of alleles and Shannon’s information index showed positive correlation with the observed number of alleles. The resolving power of the 98 SSR primers ranged from 0.72 for primer RM38 to 2.82 for primer RM592. SSR generated an average similarity of 0.460 with similarity ranging from 0.07 to 1.00. Sufficient diversity was detected among the accessions. A basic molecular database was created for upland rice genotypes, which will be useful to identify and map useful genes that are harbored by these germplasms.